커피·디저트 전문점의 브랜드 공간 요소와 체험 제공 수단의 표현정도에 관한 연구 - 소상공인, 중소기업을 중심으로 - 홍보람; Bo-ram Hong; 김시연; Si-yeun Kim (한국디자인포럼, 2025)
연구배경 국내 커피 전문점은 10만 개를 넘어섰고, 이중 다수가 소상공인·중소기업 점포이다. 선택적 소비품목에서 소비자는 품질을 넘어서 경험과 가치를 중시하며, 커피·디저트 업계도 브랜드 공간과 체험 요소의 중요성이 부각되고 있다. 이에 본 연구는 소비자 반응이 높은 소상공인 사례를 통해 브랜드 공간 구성 요소와 체험 제공 수단의 특징 및 개선 방향을 도출하고자 한다. 연구방법 연구방법으로 첫째, 소상공인, 중소기업의 커피·디저트 업계 현황을 파악하고 이들의 브랜드 공간변화 양상을 논의한다. 둘째, 선행 연구 및 문헌고찰을 통해 브랜드 공간 요소와 체험 제공 수단의 특징을 도출하고 사례분석의 틀을 제시한다. 셋째, 선정 된 5개의 사례를 분석하여 브랜드 공간 요소와 체험 제공 수단의 표현정도를 조사한다. 연구결과 사례분석 결과, 브랜드 공간 요소의 표현정도 순위는 매력성, 조화성, 전체성, 상징성, 정보성 순으로 나타났다. 분석 대상 점포들은 소비자에게 일상에서 벗어난 차별화된 경험을 제공하는 매력성을 핵심 요소로 활용하고 있었다. 체험 제공 수단의 표현정도는 제품 외관, 공간적 환경, 아이덴티티, 커뮤니케이션, 인적 요소순으로 나타났다. 특히 제품 외관은 브랜드의 정체성을 가장 일관되게 표현하는 중요한 역할을 하고 있었다. 결론 본 연구는 소상공인, 종소기업의 커피·디저트 브랜드 공간에서 매력성과 공간적 환경의 중요성, 제품외관과 공간 아이덴티티의 일관성 확보, 그리고 정보성과 인적요소의 보완 가능성을 제시하였다. 브랜드 공간이 일관된 정체성을 유지하려면 제품과 공간이 하나의 통합된 브랜드 경험을 제공해야 하며, 공간적 환경과 아이덴티티의 연결성을 높이는 전략이 필요함을 확인하였다. Background In Korea, the number of coffee shops has surpassed 100,000, with a large proportion operated by small businesses and SMEs. As consumers increasingly prioritize experience and value over product quality, this study investigates key components of brand space and experience providers based on successful small business cases. Methods As a research method, First, this study examines the current status of the coffee and dessert industry among small businesses and SMEs, and discusses the changes in their brand spaces. Second, it derives the key characteristics of brand space elements and experience providers through a review of prior studies and literature, and proposes an analytical framework for case analysis. Third, it investigates the expression intensity of brand space elements and experience providers by analyzing five selected cases. Result According to the case analysis, the expression intensity of brand space elements was ranked as follows: attractiveness, harmony, wholeness, symbolism, and informativeness. The analyzed coffee and dessert shops mainly emphasized attractiveness as a key element to provide consumers with differentiated experiences from their daily lives. For experience providers, the expression intensity followed the order of product appearance, spatial environment, identity, communication, and human factors. Notably, product appearance played a crucial role in consistently delivering the brand identity. Conclusion This study highlights the importance of attractiveness and spatial environment in the brand spaces of small and medium-sized coffee and dessert businesses. It also identifies the need to ensure consistency between product appearance and spatial identity, while suggesting the potential for improvement in informativeness and human interaction. For a brand space to maintain a coherent identity, it must offer an integrated brand experience where products and physical space work together, emphasizing the strategic need to strengthen the connection between spatial environment and brand identity.